Pengembangan Perangkat Pembelajaran Matematika Berbasis Problem Based Learning untuk Siswa Kelas VII Semester 1 SMP/MTs Materi Bilangan dan Himpunan - Armis Armis; Suhermi Suhermi (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2017)
This study aims to develop the learning of mathematics 1st junior class VII, on Numbers and Set. The learning tools developed consists of a syllabus, Lesson Plan (RPP), Sheet Teaching Materials (LMA), Student Activity Sheet (LAS), instructional media, and Authentic Assessment Sheet (LPA). This study is the research, development model 4-D which consists of four stages: Define, Design, Develop, and Disseminate. In this study the development process undertaken only to phase 3. The learning tools that have been developed, validated by two-person of experts and two practitioners then conducted a limited trial to the junior high school students in coastal areas. Data validation and students' responses collected through questionnaires which are then revised on the advice. From the results of the validation data showed the average score was 3.93 for syllabus (very valid), RPP was 3.44 (very valid), LAS was 3,67 (very valid), LMA was 3.83 (very valid), LMP was 3.92 (very valid), and the average score of the students' response was 3.76 (very practical). From the development of learning tools that have been carried out it is concluded that a learning tool developed very valid and ready to be tested on students of SMP / MTs by a larger amount.